The Effect of Leadership and Discipline on Employee Performance in KOI the’ North Jakarta Region - Anim Purwanto; Uswah Uswah (Jurnal Mantik, 2021)
The purpose of this study was to analyze and examine the effect of (1) leadership on employee performance, (2) discipline on employee performance, and (3) leadership on discipline. The method used is a quantitative method. The sample in the study was 100 respondents with the selection of samples by random sampling. The technique of collecting data is by interviewing and distributing questionnaires through google form. The data analysis technique in this study uses Partial Least Square (PLS) which is processed with the help of Smart PLS software. The result of this study prove that (1) leadership has a positive an significant effect on employee performance. If the leadership has increased, the employee performance will increase, (2) discipline has a positive and significant effect on employee performance. If discipline improved, employee performance will also increase, and (3) leadership has a positive and significant on discipline. The better of leadership so discipline of employee will increase.